The Constitutional Relationships Mandate Regarding the Implementation of Oil and Gas Investments in Indonesia - Jaelani, Abdul Kadir; Manumayoso, Bambang; Karjoko, Lego (KnE Social Sciences, 2024)
The meeting of interests between the Government of Indonesia (cq. The Unitary State of the Republic of Indonesia) and investors in the field of oil and gas investment in Indonesia is a meeting with relatively different final objectives, but business cooperation that complements each other creates synergies, and is mutually beneficial for each other’s interests, according to a mutually agreed-upon agreement or contract. This study will investigate the relationship between Indonesian constitutional mandates and the implementation of oil and gas investments. According to the 1945 Constitution of the Republic of Indonesia and Pancasila, the study demonstrates that natural resources (SDA) are capital for national economic development. Based on Pancasila and the 1945 Constitution of the Republic of Indonesia, the development of the national economy is a part of the endeavor to realize the just and prosperous welfare of the people. Keywords: constitution, national economy, oil, gas